Interferences of acquisitive experiences of mother tongue to non-Chinese learners in learning Chinese grammar - Lim, Zu Ying (2011)
Acquisition of mother tongue influenced non-Chinese learbers in learning Chinese grammar is the main topic will be investigated in this paper. The interferences of acquisitive experiences of mother tongue non-Chinese learners can be divided to positive transfer and negative transfer. The most difficult task for non-Chinese learber to master Chinese is learning Chines Grammar. From the observation of teaching practice, this research found that non-Chinese learners in understanding and constructing of Chinese sentence intterupted by their mother tongue syntax pattern, as a result Chinese sentences which constructed by non-Chinese learners, from logical thinking and structure of Chinese sentences, both of this two aspects were not meet with the Chinese grammar specification and normally Chinese sentences constructed by them have plenty of grammatical problems and for the purpose of learning of learning Chinese language as a target language still far from the goal. The gap has reflected that the gramatical errors which appeared in Chinese sentences constructed by non-Chinese learners and all these errors will be analyzed in this paper. According to the findings of this research, the generation of these Chinese grammatical errors is closely related to the cognitive psychology of non-Chinese learners, they are unable to master the Chinese grammar from the aspect of Chinese characteristics and in addition they adopted the acquisitive method of mother tongue had interrupted the learning process of non-Chinese learners in mastering Chinese grammar. This paper tried to reveal the grammatical errors which normally existed in Chinese sentences constructed by non-Chinese learners, and the discussion of this study are based on be structure' sentence, of structural particle' sentence and De as a morpheme to build up a word phrase these three aspects to analyzed their Chinese grammatical errors.